Effect of Cattle Breeds on Milk Composition and Technological Characteristics in China - Yang, T. X. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
Cattle breeds have a striking effect on milk, including milk composition and technological characteristics. This study aims to compare milk composition, acidification activity, viscosity, milk dispersion system stability and casein molecular weight among three buffalo breeds in China. The technological characteristics of milk produced by three cattle breeds of river buffalo (Murrah), crossbreed 1st generation (F(1)), crossbreed multiple generation (F(H), H≥3) buffaloes were investigated. Cattle breeds showed evident effect on milk protein, fat and total solids content, but little effect on most of buffalo casein molecular weight. Milk fat, protein content and the viscosity of buffalo milk from river buffalo were lower than those of F(1) and F(H), so was the buffer capacity. The viscosity was negatively correlated to temperature and concentration. Results of stability coefficient showed that milk dispersion system had the best dynamic stability characteristics under pH 6.6 and 6 times dilution, while zeta potential of Murrah milk was slightly higher than that of hybrid offspring (F(1), F(H)). SDS-PAGE results showed that buffalo α(s)-casein had a slightly faster mobility than standard α(s)-casein; while buffalo β-casein showed a slightly slower mobility than standard β-casein. There is no clear differences in molecular weight of α(s)-, β-, and κ-casein among Murrah, F(1) and F(H).